THE DESIGN OF RADIOLOGY VIEWING BOX USING POTENTIOMETER SYSTEM - Diartama, Anak Agung Aris; Suswaty, Susy; Priantoro, Win; Sudiyono, Sudiyono; Sugiyanto, Sugiyanto; Anwar, Muhammad Choiroel; Latifah, Leny; Santjaka, Aris; Amri, Faisal; Mulyantoro, Donny Kristanto (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: In the process of work to gain the maximum results, a radiologist needs a viewing box tool to read radiographs. Aims: to create a viewing box tool by using a potentiometer system. Methods: This study used applied research method by creating and using the design of viewing box tool by using a potentiometer system and testing the viewing box tool created by using a Lux meter and 15 respondents consisting of five radiologists and 10 radiographers who should fulfill the questionnaire form. Results: The mean of viewing box illumination reached 220 lux. The results of the questionnaire showed that 100% radiologist gave an A (excellent) and expressed that the viewing box tool created could be used properly and 90% radiographers provided an A (excellent) and expressed that the viewing box tool created could be used properly, while 10% radiographer gave a value of B (moderate). Conclusion: viewing box tool created could be used properly and obtained optimal results as a tool in reading radiographs. Potentiometer system contained in the viewing box was very helpful in reading radiographs because it allowed to adjust the light intensity according to user needs.Â